Pengembangan Buku Pengayaan Pengenalan Makanan Tradisional Bagi Guru Paud Di KB/TK Al-Fadholi Malang - Iing Fajar Wahyuni; Endang Poerwanti (Jurnal Kebijakan dan Pengembangan Pendidikan, 2016)
Abstract: The research aims to develop an introduction to traditional food introduction books for PAUD teachers. The research method used in this study refers to the research and development (R&D) research model. This research was conducted at KB / TK Al-Fadholi Malang. Research subjects included media experts, material experts, and KB / TK Al-Fadholi Malang and Cluster III Teachers in Lowokwaru District (n = 25). Data analysis techniques using qualitative descriptive analysis, descriptive statistical analysis, and paired t-test. The results of this study indicate that the development of a traditional food introduction enrichment book for PAUD teachers, namely the percentage of the feasibility of expert test obtained by 95%, the percentage of the feasibility of limited trials obtained by 96% and experimental trials obtained p = 0,000 (p <0.05). The media Traditional Food Introduction Enrichment Book for PAUD Teachers based on its applicability is categorized as appropriate with high qualifications and can be applied as a supporting medium for teacher activities in introducing and accustoming early childhood to consuming traditional foods.Keywords: Enrichment Books, Traditional Foods, Introduction to Traditional Foods, PAUD Abstrak:Penelitian ini bertujuan untuk mengembangkan buku pengayaan pengenalan makanan tradisional bagi Guru PAUD. Metode penelitian yang digunakan dalam penelitian ini mengacu pada model penelitian research and development (R&D). Penelitian ini dilakukan di KB/TK Al-Fadholi Malang. Subyek penelitian meliputi ahli media, ahli materi, dan Guru KB/TK Al-Fadholi Malang serta Guru gugus III Kecamatan Lowokwaru (n=25). Tehnikanalisa data menggunakan Analisis deskriptif kualitatif, analisis statistik deskriptif, dan paired t-test. Hasil penelitian ini menunjukkan bahwa pengembangan buku pengayaan pengenalan makanan tradisional bagi Guru PAUD yakni diperoleh prosentasi kelayakan uji ahli 95%, prosentase kelayakan uji coba terbatas diperoleh 96% dan uji coba eksperimen diperoleh nilai p= 0.000 (p<0.05). MediaBuku Pengayaan Pengenalan Makanan Tradisional bagi Guru PAUD berdasarkan keterterapannya dikategorikan layak dengan kualifikasi tinggi dan dapat diaplikasikan sebagai media penunjang aktivitas guru dalam mengenalkan dan membiasakan anak usia dini untuk mengkonsumsi makanan tradisional.Kata kunci:Buku Pengayaan, Makanan Tradisional, Pengenalan Makanan Tradisional, PAUD